2017
DOI: 10.1111/1759-7714.12414
|View full text |Cite
|
Sign up to set email alerts
|

Is chronic kidney disease an adverse factor in lung cancer clinical outcome? A propensity score matching study

Abstract: BackgroundComorbidity has a great impact on lung cancer survival. Renal function status may affect treatment decisions and drug toxicity. The survival outcome in lung cancer patients with coexisting chronic kidney disease (CKD) has not been fully evaluated. We hypothesized that CKD is an independent risk factor for mortality in patients with lung cancer.MethodsA retrospective, propensity‐matched study of 434 patients diagnosed between June 2004 and May 2012 was conducted. CKD was defined as estimated glomerula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In a previous retrospective report using the CG formula, Lu et al . found similar rates of survival between CKD and non‐CKD patients . Xie et al .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In a previous retrospective report using the CG formula, Lu et al . found similar rates of survival between CKD and non‐CKD patients . Xie et al .…”
Section: Discussionmentioning
confidence: 81%
“…Lu et al . found a 6% increased risk of death for CKD patients; however, this result was not statistically significant (HR 1.06, 95% CI 0.93–1.22; P = 0.41) . In a recent population‐based cohort study in Taiwan of lung cancer patients with coexisting CKD, Wei et al .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, it has been confirmed that lung cancer and CKD may have a similar course and survival in comparison with the patients with lung cancer without CKD, which it means that these two diseases could receive the same benefit from treatment (24). However, it has also approved that CKD could not be an independent risk factor for survival in patients with lung cancer (25). Moreover, progressive renal failure was observed in patients with lung adenocarcinoma (26).…”
Section: Lung Cancer and Kidneymentioning
confidence: 98%